Mainstreaming the informal gun making sector in Danao, Cebu - Gantuangko, Neri R. (Danyag : Journal of Humanities and Social Sciences, 2002)
This paper analyzes the nature as well as socio-cultural, politico-legal and economic implications of the informal firearms activity in Danao City, Cebu. It establishes the profile of some manufacturers of hand guns (locally called "paltik") vis-a-vis perceptions of stakeholders towards the informal gun making sector, with the end view of presenting recommendations to address the issues and problems attendant to the informality of this livelihood. Thirty (30) gun makers in the informal sector, 30 gun makers from the Workers' League of Danao Multi-purpose Cooperative and 50 other stakeholders were interviewed. It is estimated that approximately 25% (8,000) of the total working population of Danao City are directly or indirectly involved in this clandestine, almost crude, but lucrative activity, which caters to a domestic and an international market. The findings indicate that the informal firearms manufacturers in Danao are willing to diversify into other gainful occupations-preferably in the metals craft industry - if offered the opportunity. All respondents of the study, including other stakeholders, argue that this craft should be harnessed by the national government. However, there appears to be no serious effort on the part of the national government to address this sector of the informal economy notwithstanding its growing size and potential contribution to the government coffers. A context for a local government initiative that can apply to the informal economy sector including the informal gun making craft and livelihood is proposed.